2010
DOI: 10.2337/dc10-0814
|View full text |Cite
|
Sign up to set email alerts
|

No Protective Effect of Calcitriol on β-Cell Function in Recent-Onset Type 1 Diabetes

Abstract: OBJECTIVEWe investigated whether supplementation of the active form of vitamin D (calcitriol) in recent-onset type 1 diabetes can protect β-cell function evaluated by C-peptide and improve glycemic control assessed by A1C and insulin requirement.RESEARCH DESIGN AND METHODSThirty-four subjects (aged 11–35 years, median 18 years) with recent-onset type 1 diabetes and high basal C-peptide >0.25 nmol/l were randomized in a double-blind trial to 0.25 μg/day calcitriol or placebo and followed-up for 2 years.RESULTSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 7 publications
4
95
3
2
Order By: Relevance
“…Research in Germany and Italy also obtained similar results [31,32]. This is due to the duration of disease in this study subjects averaged still a decade so obtained low levels of C-peptide despite the increase of 25(OH)D 3 and this indicates that the progressive destruction of pancreatic β cells occur mainly in the first years of the emergence T1DM disease [38].…”
Section: Subject Characteristicssupporting
confidence: 71%
See 1 more Smart Citation
“…Research in Germany and Italy also obtained similar results [31,32]. This is due to the duration of disease in this study subjects averaged still a decade so obtained low levels of C-peptide despite the increase of 25(OH)D 3 and this indicates that the progressive destruction of pancreatic β cells occur mainly in the first years of the emergence T1DM disease [38].…”
Section: Subject Characteristicssupporting
confidence: 71%
“…In another study, 34 patients were newly diagnosed with T1DM in a double-blind trial with calcitriol 0.25 µg/day or placebo and followed for 2 years. The levels of C-peptide fell significantly, but in both groups had similar levels, with no significant difference [32].…”
Section: Subject Characteristicsmentioning
confidence: 94%
“…In a clinical setting, two recent trials found no significant effect of 1,25(OH) 2 D on the preservation of β-cell function after type 1 diabetes onset (58,59). Nevertheless, the dose and mechanistic action of vitamin D are still under discussion.…”
Section: Vitamin D and Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…Even though there was a decrease in the insulin requirements at 3 and 6 months in the calcitriol treated group, at the end of the first year there was no difference between the C-peptide levels or hemoglobin A1c between the two groups (Pitocco et al, 2006). Bizzarri et al investigated whether supplementation with calcitriol in recent onset autoimmune diabetes has a protective effect on the pancreatic beta cells and found that, at the doses used in the study, calcitriol did not confer protection against the autoimmune destruction of the beta cells (Bizzarri et al, 2010). In Germany, Walter et al supplemented newly diagnosed adult patients with 1,25(OH)2D3 for 18 months.…”
Section: Clinical Studies -Vitamin D and Type 1 Diabetesmentioning
confidence: 99%